MENTAL HEALTH COMORBIDITY IN A CANADIAN COURT - Leung, Pauline; Khalifa, Najat; Hassan, Tariq (Journal of Pakistan Psychiatric Society, 2022)
ObjectiveOver the past two decades, Canada has seen a rapid growth in problem-solving courts. Such courts are predicated on the rationale that certain populations of individuals who come into contact with the law do so not out of choice, but because of personal circumstance. One prominent example of a problem-solving court is the mental health court. the current investigation serves as a preliminary look into the needs of individuals in contact with the law in southeastern Ontario, Canada. At the time of the writing of this report, no mental health courts had yet been established in the region. We sought to assess the need for such a court by reviewing some key demographics in a sample of offenders in a ‘guilty plea’ court.Design:To this end, data from guilty plea court was collected over the course of several months. The data was publicly available and therefore university ethics though enquired was not required. At the completion of data collection, information from 79 court cases had been documented. These cases were coded for the presence or absence of identified mental health concerns, and subsequent analysis was conducted to discern whether mental health status could predict the type and severity of charges accrued. Results:Of the 79 cases, 24 individuals attending guilty plea court were identified as presenting with mental illnessConclusion:Everything taken together, the current study highlights the need and utility for mental health courts. We offer empirical evidence of such a need, and add to the slowly growing—and altogether much-needed—body of literature surrounding mental health courts in Canada.